RISK FACTORS FOR UNDERDIAGNOSIS OF DIABETES: BASED ON THE KOREAN NATIONAL HEALTH AND NUTRITION EXAMINATION SURVEY. (11th November 2018) - Min, D; Cho, E
Abstract: Diabetes is a widespread disease and is known to have many complications and high mortality. Therefore, prevention, early diagnosis, and treatment of diabetes are very important. The diagnostic criterion for diabetes is HbA1c (≥6.5). There are many people with diabetes who have not been diagnosed with the disease. This study aimed to analyze the risk factors for underdiagnosis, classifying diabetic patients who were not diagnosed with diabetes into normal group and risk group using data from the 6th Korea National Health and Nutrition Examination Survey (2013–2015). We included 11, 298 subjects aged 30 years or older who did not have diabetes, as diagnosed by doctors, and had undergone HbA1c screening. This study was analyzed by reflecting the weight that the sample was presented to represent Korea in KNHANES. The differences between the two groups were analyzed using t-test and chi-squared test (X2), and risk factors for underdiagnosis of diabetes were examined by logistic regression analysis. Risk factors were: age (Odds Ratio(OR): 1.06, 95% Confidence Interval (CI): 1.04–1.08), Medical Aid (OR: 2.77, 95% CI: 1.25–6.14), presence of family history of diabetes (OR: 1.97, 95% CI: 1.36–2.84), serum triglyceride (OR: 1.01, 95% CI: 1.01–1.03), serum HDL (OR: 0.96, 95% CI: 0.95–0.98), smoking status (OR: 1.85, 95% CI: 1.20–2.85), and presence of health checkups (OR: 1.41, 95% CI: 1.01–2.00). Therefore, in order to prevent diabetes and enable healthy life, it is necessary to establish a diabetes prevention program for vulnerable people and to implement health-related policies such as smoking cessation and regular checkups.